Einführung - Eikermann, Larissa (Belgischer Symbolismus zum Be/Greifen nah: Museumskoffer zum Werk von Léon Spiliaert und George Minne)

Children’s Information-Related Internet Use at Home: The Role of the Quantity and Quality of Parental Support and Children’s Motivation - Gruchel, Nicole; Kurock, Ricarda; Bonanati, Sabrina; Buhl, Heike M. (Journal of Research in Childhood Education)
Children’s information-related internet use positively affects their acquisition of computer- and information-related skills. Nevertheless, this use still occurs predominantly in the family context. Parents’ support of their children’s internet use can motivate them to use the internet for information-related purposes. However, while parents’ support seems to be important, the quantity and quality of parental support have been shown to have different associations with children’s motivation. Thus, the goal of the current study was to examine the relationship between parents’ support (quantity and quality), children’s motivation to engage in information-related internet use, and children’s actual information-related internet use (practical and school- or learning-related use) using structural equation modeling. In addition, we examined the mediating effects of children’s motivation. Specifically, 492 12-year-old German children answered a paper-and-pencil questionnaire. We found positive associations between the quantity and quality of parents’ support and children’s intrinsic and extrinsic motivation, while only structure-giving support was found to be related to children’s intrinsic motivation. The quantity of support was directly related to children’s school- or learning-related use, while intrinsic motivation was associated with both forms of information-related internet use. Furthermore, we confirmed that children’s motivation is an important mediator in this context. The implications of these findings for parents and children are considered.
Keywords: children's motivation; information-related internet use; quality of parental support; quantity of parental support

Was motiviert CoP-Mitglieder? Motivationale Bedingungsfaktoren für die Mitarbeit in Communities of Practice in der Lehrkräftebildung - Raneck-Kuhlmann, A.; Niemann, Jan; Buhl, Heike M.; Eickelmann, Birgit; Drossel, Kerstin (Lehrkräftebildung in der digitalen Welt – zukunftsorientierte Forschungs- und Praxisperspektiven)

The mental representation of the object of explanation in the process of co-constructive explanations - Schaffer, Michael; Buhl, Heike M. (53rd DGPs Congress - Abstracts)

Elterliche Unterstützung beim Lernen mit digitalen Medien - Kamin, Anna-Maria; Meister, Dorothee M.; Buhl, Heike M. (Medien - Bildung - Forschung)

Förderung der Selbstreflexion und Weiterentwicklungsorientierung durch reflexionsorientierte Workshops im Lehramtsstudium - Kleine, Sabrina M; Sohlau, Sylvia; Seifert, Andreas; Buhl, Heike M. (Herausforderung Lehrer*innenbildung - Zeitschrift zur Konzeption, Gestaltung und Diskussion)
In der Professionalisierung von Lehrkräften ist die Selbst-reflexion eine wesentliche Voraussetzung, da sie zentral für die Weiterentwicklung der eigenen Kompetenzen ist. Daraus ergibt sich die Notwendigkeit, bereits in der ersten Phase der Lehrkräftebildung die Selbstreflexion und die Weiterentwicklungsorientierung zu fördern. Hierzu sind auf Grund des sozialen Settings gezielte reflexionsorientierte Workshops chancenreich. Um die Effekte von reflexionsorientierten Workshops und dabei den Zusammenhang zwischen der Selbst-reflexion und der Weiterentwicklungsorientierung zu überprüfen, wurden anhand einer Stichprobe von N = 646 Lehramtsstudierenden die Entwicklung der Selbst-reflexion und Weiterentwicklungsorientierung beim Besuch von Workshops zu überfachlichen Kompetenzen untersucht. Die Datenerhebung erfolgte vor, direkt nach und erneut vier bis sechs Wochen nach den reflexionsorientierten Workshops mittels eines Fragebogens. Durch Varianzanalysen können in Bezug auf die Selbst-reflexion direkt nach den Workshops signifikante Effekte sowie eine konstante Ausprägung vier bis sechs Wochen später nachgewiesen werden. Weiterhin konnte ein signifikanter Anstieg bei der Weiterentwicklungsorientierung über die drei Messzeitpunkte verzeichnet werden. Ebenso zeigte sich ein positiver Effekt der Selbstreflexion auf den Anstieg der Weiterentwicklungsorientierung.

Blogpost: "Praxisseminar zur Konzeption und Organisation wissenschaftlicher Tagungen des Fachbereichs Komparatistik an der Universität Paderborn (Sommersemester 2024)" - Spener, Anna Maria

Widersprüchliche Anforderungen sichtbar machen Making contradictory requirements visible - Richter, Susanne (MedienPädagogik: Zeitschrift für Theorie und Praxis der Medienbildung)
Soziale Plattformen und insbesondere Beauty Content – also Beiträge, in denen Praktiken des Schönheitshandelns thematisiert werden – generieren pädagogische Aufmerksamkeit im Schnittpunkt von Gender- und Medienpädagogik. Damit bietet die Beauty Community in zweierlei Hinsicht Ansatzpunkte für die Frage nach postdigitalen Impulsen für die Pädagogik: Zum einen ist sie Gegenstand pädagogischer Arbeit, zum anderen ein neuer sozialer Raum, der komplexe Analysen der Performances und Aushandlungen sozialer- und Geschlechterordnungen ermöglicht. In diesem Beitrag werden die Befunde einer geschlechtersoziologischen Studie der YouTube Beauty Community (Richter 2021) im Hinblick auf die Frage nach pädagogischen Implikationen postdigitaler Kultur gelesen. Dafür werden zunächst pädagogische Problematisierungen der Beauty Community dargelegt und anschliessend durch ausgewählte Befunde der fokussierten Studie kontrastiert, um eine produktive Perspektive auf diese Probleme zu erarbeiten: Die Akteur:innen der Community werden darin sichtbar als in Widersprüchen verortet, die Herstellung von Souveränität wird als zentraler Wert verhandelt. Pädagogische Implikationen postdigitaler Kultur, so wird abschliessend argumentiert, liegen im analytischen Potenzial der Untersuchungen digitaler Arenen, das sowohl für die Erforschung gegenwärtiger gesellschaftlicher Transformationen als auch als Grundlage für pädagogisches Handeln eingesetzt werden kann – nicht zuletzt in Bezug auf Herausforderungen, die mit der Entstehung und Etablierung dieser neuen Arenen und ihrer Ausbreitung einhergehen.

Prozessüberwachte Eigenschaftseinstellung beim Clinchen der ausscheidungshärtbaren Aluminiumlegierung EN AW-6014 - Lüder, Stephan; Kalich, Jan; Oesterle, Hannes; Schmale, Hans Christian (Tagung Werkstoffprüfung 2024: Werkstoffe und Bauteile auf dem Prüfstand, Prüftechnik – Kennwertermittlung – Schadensvermeidung)
Die Wandlungsfähigkeit einer Prozesskette erfordert Fügeverbindungen mit gezielt einstellbaren mechanischen, elektrischen, thermischen oder chemischen Eigenschaften. Dieser Beitrag beschreibt die Untersuchungen, inwiefern beim Clinchen zweier Bleche aus der ausscheidungshärtbaren Aluminiumlegierung EN AW-6014 bereits auf Basis der Prozessüberwachung des Kraft-Weg-Verlaufs bzw. des sich daraus ergebenden Energieeintrags auf die mechanischen und elektrischen Eigenschaften der Fügeverbindung geschlossen werden kann. An einer ausgewählten Fügeaufgabe werden im Stufenversuch die gegenseitigen Abhängigkeiten der einzelnen Einflussgrößen sowie des Wärmebehandlungszustands aufgezeigt. Dabei wird zwischen den Bindemechanismen Formschluss und Kraftschluss unterschieden. Die Formschlusskomponente wird anhand der geometrischen Kenngrößen wie Bodendicke, Halsdicke und Hinterschnitt in Mikroskopieuntersuchungen an Schliffbildern und den mechanischen Eigenschaften der Fügeverbindung untersucht, die im Scherzug- und Kopfzugversuch bestimmt werden. Dazu erfolgt zudem die Charakterisierung der Versagensbilder. Zur Quantifizierung der Kraftschlusskomponente der Fügeverbindung werden das Losbrechmoment im Torsionsversuch und der elektrische Widerstand mittels Vier-Leiter-Methode ermittelt und korreliert.
Keywords: Clinchen; Aluminium; Stufensetzversuch; Bindemechanismus; Formschluss; Kraftschluss; Zugversuch; Torsionsversuch; Widerstandsmessung

ROCES: Robust Class Expression Synthesis in Description Logics via Iterative Sampling - KOUAGOU, N'Dah Jean; Heindorf, Stefan; Demir, Caglar; Ngonga Ngomo, Axel-Cyrille (Proceedings of the Thirty-ThirdInternational Joint Conference on Artificial Intelligence)
We consider the problem of class expression learning using cardinality-minimal sets of examples. Recent class expression learning approaches employ deep neural networks and have demonstrated tremendous performance improvements in execution time and quality of the computed solutions. However, they lack generalization capabilities when it comes to the number of examples used in a learning problem, i.e., they often perform poorly on unseen learning problems where only a few examples are given. In this work, we propose a generalization of the classical class expression learning problem to address the limitations above. In short, our generalized learning problem (GLP) forces learning systems to solve the classical class expression learning problem using the smallest possible subsets of examples, thereby improving the learning systems' ability to solve unseen learning problems with arbitrary numbers of examples. Moreover, we develop ROCES, a learning algorithm for synthesis-based approaches to solve GLP. Experimental results suggest that post training, ROCES outperforms existing synthesis-based approaches on out-of-distribution learning problems while remaining highly competitive overall.

„Flandern“ und der Jansenismus. Eine Hotspot inmitten der Repression? - Huybrechts, Yves; Resch, Pauline (BelgienNet)
Vor langer Zeit, im 17. und im 18. Jahrhundert, tobte innerhalb der Strukturen der Katholischen Kirche in West-Europa einen Kampf um die deutung und den Umgang mit der göttlichen Gnade sowie dem Sündenbegriff. Dieser Kampf hatte viele Auslöser, aber keiner war so umstritten wie die Bewegung mit dem Namen "Jansenismus". Heute ist sie beinahe der Vergessenheit anheimgefallen, aber lange Zeit hatte sie (und die Bekämpfung dieser Bewegung) einen deutlichen Einfluss auf "Staat und Kirche". War es aber eine Bewegung? Und gegen wen richtete sie sich? Warum wurde sie so heftig bekämpft? In diesem Beitrag geht es um diese Fragen, aber vor allem um den vergessenen Geburtsorts dieser Bewegung: in Löwen, einer Stadt im heutigen Flandern.

Das Geflecht der Zollpolitik in den Spanischen Niederlanden. Die Wirtschaftskonferenz von 1699 am Brüsseler Hof - Huybrechts, Yves

BelgienNet en BeNeLuxNet – de geschiedenis van de Benelux voor een Duits publiek op het internet - Huybrechts, Yves

A School Student Essay Corpus for Analyzing Interactions of Argumentative Structure and Quality. - Rezat, Sara; Stahl, Maja; Michel, Nadine; Kilsbach, Sebastian; Schmidtke, Julian; Wachsmuth, Henning

Implementing Strategic Environmental Assessment (SEA) in the Global South, a challenge: Nicaragua as a case study. - Díaz Canales, Edith Benjamina; Avila , Alfredo; Schlüter, Sabine; Lacayo, Erick; Schlüter, Alexander (19th Conference on Sustainable Development of Energy, Water and Environment Systems)

Digital participation and communication disorders across the lifespan

Digital participation of brain tumour patients in the assessment and treatment of communication disorders - Weiss Lucas, C; Kochs, S; Jost, J; Loução, R; Kocher, M; Goldbrunner, R; Wiewrodt, D; Jonas, Kristina (Frontiers in. Psychology)

Editorial: Digital participation and communication disorders across the lifespan - Jonas, Kristina; Jaecks, P; Frieg, H (Frontiers in. Psychology)

Anthropological Dimension of Wartime Ecocide: Ecofeminist Methodological Assessments - Karpenko, Kateryna I.; Hagengruber, Ruth Edith; Nielsen, Cynthia R. (Anthropological Measurements of Philosophical Research)
The authors aim to disclose the anthropological dimension of ecocide during and after Russia’s war against Ukraine, relying on the multidisciplinary practices and intellectual production of ecofeminist women thinkers, including philosophers, sociologists, historians, psychologists, and others. The theoretical basis methodological approaches in philosophical anthropology, phenomenology, analytical philosophy, communicative philosophy, existentialism, ethics of justice, and ethics of care determine the study’s theoretical basis. Originality. For the first time, a systematic analysis of the anthropological dimension of ecocide has been carried out based on ecofeminist methodology. The specifics of the Ukrainian resistance to ecocide were revealed as part of a single struggle – an anti-imperial and ecological struggle for independence and prosperity. It is emphasized that during the war, the opposition to ecocide is a component of the fight for national sovereignty and territorial integrity of the country, and therefore, the ideas of pacifism in this period are subordinated to this primary goal. After the war, preventing threats of ecocide should become an integral part of the struggle for stable peace and prosperity. Ecofeminist pacifist perspectives should be a priority among the most essential goals for that period. Conclusions. Ecofeminist methodological assessments offer valuable insights into the anthropological dimension of ecocide in wartime and post-war contexts, highlighting the complex interplay between gender, violence, and environmental destruction. By focusing on the experiences and perspectives of women and marginalized communities, ecofeminist analyses contribute to a more holistic understanding of ecocide and its impacts on both human populations and ecosystems.

Teaching Women Philosophers—Ideas and Concepts from Women Philosophers’ Writings Over 2000 Years - Hagengruber, Ruth Edith (Teaching Women Philosophers. Women in the History of Philosophy and Sciences.)
Why should the philosophy of the Pythagoreans be reduced to Pythagoras alone? Why do we learn about the ego only from Husserl and not from Conrad-Martius? What do we know about free will from Helene Druskowitz and why is Émilie Du Châtelet unknown to us? Many of the philosophers in this collection were celebrities in their own time. What can we gain from rediscovering the knowledge of women philosophers? Philosophy reflects the foundations on which we organise our world. There is no doubt that women create structures that shape our world. Over the centuries, women thinkers have formulated ideas and concepts to explain our world and to call for its reorganisation. This collection offers a selection of these ideas and concepts from over 2000 years. The new history of philosophy emerges in this way. It provides the basis for teaching and future research. Rooted in the past, it can use that experience to contribute to a new and better way forward.